Penetapan Alam Sebagai Subjek Hukum - Miftakhul Shodikin (CV. Era Digital Nusantara, 2023)
Abstract: Legal subjects who are believed to be the holders of rights and obligations in fact, over time always experience expansion or development. After women were recognized as having legal status and corporations as non-human legal subjects, a new legal subject emerged, namely: nature. Ecuador gave the rights to nature that were embedded in the 2008 constitutional amendments, the Whanganui River in New Zealand was recognized as a legal subject with representatives of the Maori tribe, and the Ganges and Yamuna Rivers and their attributes through a decision in HC Uttarakhand India established them as legal subjects. These three legal precedents are important breakthroughs in the concept of